Representasi Kritik Politik terhadap Isu Esemka dan Mahkamah Konstitusi melalui Meme di Instagram - Putri, Dewi Ananda; Fauzi, Agus Machfud (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2025)
Online pop culture has grown rapidly in the digital era and has changed the way people express their opinions, especially when discussing political issues. One of the most commonly used forms of expression is memes, as they are easy to understand, light, yet capable of delivering sharp criticism. This study examines the meanings contained in the meme “In the past, the father went to the capital riding ESEMKA, now the son goes to the capital riding EMKA,” uploaded by the Instagram account @komikkitaig. Using Roland Barthes’ semiotic analysis, this research explores meaning on three levels. At the denotative level, the meme presents a symbolic comparison between the father through the “ESEMKA” vehicle and the son through “EMKA” as a representation of the Constitutional Court. At the connotative level, the symbols “ESEMKA EMKA” point to criticism of political projects that never materialized and the rise of dynastic politics. Meanwhile, at the mythical level, the meme shows how political power in Indonesia is often wrapped in symbolic development narratives. The findings suggest that memes function as visual satire capable of delivering political criticism without direct confrontation. Their simplicity and humor make the critique more accessible, as reflected in public responses such as reposts and online discussions that help reinforce the circulation of resistance discourses in digital spaces.